Acceptability about the use of generic drugs and its challenges in the pharmaceutical market (Research, Society and Development, 2022)
Introduction: Drugs are pharmaceutical forms obtained for the therapeutic purpose for diagnostic purposes, so drugs are indispensable for human health. Then the generic drug policy in Brazil, implemented by law 9.787/99 established generic as identical to the reference, aiming at a greater introduction of drugs throughout the Brazilian territory ensuring a higher quality of life for the population. Anvisa guarantees the effectiveness of these drugs through bioequivalence testing, thus ensuring their interchangeability. Objective: To make an analysis about the acceptability of society in relation to the use of generic drugs and what are its challenges in the pharmaceutical market. Methodology: Refers to a bibliographic literature research, of the type integrative, qualitative and exploratory review, carried out in the databases: Scielo, Google scholar and Anvisa website. Result of discussions: Although it has been noted that the acceptance of generic drugs have grown since their arrival here in Brazil, it was observed the importance that health professionals have ahead to help expand the knowledge of the quality of generic drugs and that they are fully interchangeable as original medicine. Conclusion: It is concluded, then, that generics are of great importance for health promotion and that knowledge about their efficacy has increased over the years, but it is of paramount importance for physicians and pharmacists to explain the effectiveness of these drugs so that this acceptance can have more confidence.